Design of the beam delivery system for the international linear collider - Seryi, A; Amann, J; Arnold, R; Asiri, F; Bane, K; Bellomo, P; Doyle, E; Fasso, A; Jonghoon, K; Keller, L; Ko, K; Li, Z; et al. (2007)
The beam delivery system for the linear collider focuses beams to nanometer sizes at its interaction point, collimates the beam halo to provide acceptable background in the detector and has a provision for state-of-the art beam instrumentation in order to reach the ILCs physics goals. This paper describes the design details and status of the baseline configuration considered for the reference design and also lists alternatives. ©2007 IEEE.